Confirmatory identification and antibiotics resistance profiling of Pseudomonas aeruginosa: a laboratory-based study - Hafsa Abdulhamid Abdulsalam (Acta Scientiarum: Biological Sciences)
Pseudomonas aeruginosa is a significant opportunistic pathogen frequently found in hospital environments and sewage systems, posing a challenge due to its intrinsic resistance to multiple antibiotics. Five isolates of Pseudomonas aeruginosa were collected from the Ahmadu Bello University Teaching Hospital, Shika Zaria and subjected to Gram staining and biochemical tests for initial identification. Four isolates were confirmed to be Pseudomonas aeruginosa based on these tests. Antibiotic susceptibility testing was performed to assess their resistance profiles, focusing on Imipenem and Ofloxacin. All four confirmed Pseudomonas aeruginosa isolates demonstrated resistance to Imipenem, a carbapenem antibiotic commonly used in clinical settings. Conversely, these isolates showed sensitivity to Ofloxacin, an alternative antibiotic with implications for treatment strategies against Pseudomonas aeruginosa infections. The observed resistance to Imipenem underscores ongoing challenges in treating Pseudomonas aeruginosa infections, emphasizing the need for alternative therapeutic options such as phage therapy.